Excellent Response to Plasma Exchange in Three Patients With Enterovirus-71 Neurological Disease - Pascual-Goñi, Elba; Josa, Maria; Launes, Cristian; Querol, Luis; del Cuerpo, Marga; Bosch, M. Alba; Jordan, Iolanda; Turón-Viñas, Eulàlia (Frontiers in Neurology, 2019)
The clinical spectrum of Enterovirus-71-associated neurological disease includes acute flaccid paralysis, encephalomyelitis, or brainstem encephalitis with autonomic dysfunction. As no specific antiviral treatments are available, intravenous human immunoglobulin is used in early stages of the illness, decreasing serum proinflammatory cytokines and improving clinical outcomes. Plasma exchange aims to eliminate pathogenic autoantibodies and proinflammatory cytokines, and is used in diverse immune-mediated neurologic conditions. However, its effect in Enterovirus-71 infections is unknown. We report three cases of severe Enterovirus-71 neurological disease treated with plasma exchange during an outbreak in Catalonia (Spain) in 2016. We observed a striking improvement in all three patients within 48 hours of starting plasma exchange. Patients received four to six sessions every other day. Good outcomes were confirmed at the one-year follow-up visit. Our observations suggest that plasma exchange is an effective complementary therapy for severe Enterovirus-71 neurological disease.